Snow White - Torres, Melissa; Lanza, Barbara (New York Scholastic Inc., 2003)
A princess takes refuge from her wicked stepmother in the cottage of seven dwarfs.
Cartwheel books.
Keywords: Fairy tales; Folklore -- Germany